2018
DOI: 10.48550/arxiv.1810.03622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stationary Phase Method in Discrete Wigner Functions and Classical Simulation of Quantum Circuits

Lucas Kocia,
Peter Love

Abstract: We apply the periodized stationary phase method to discrete Wigner functions of systems with odd prime dimension using results from p-adic number theory. We derive the Wigner-Weyl-Moyal (WWM) formalism with higher order corrections representing contextual corrections to noncontextual Clifford operations. We apply this formalism to a subset of unitaries that include diagonal gates such as the π 8 gates. We characterize the stationary phase critical points as a quantum resource injecting contextuality and show t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…In this direction, we previously showed that odd-primed dimensional qudit T gate magic states have the same stabilizer rank for t = 1 and t = 2 as has been found for qubits up to the exponential base factor-2 αt ↔ d αt , i.e. (χ 1 ) t = d t and (χ 2 ) t = d 0.5t [9]. In fact, we proved that stabilizer decompositions that achieve these stabilizer ranks for t = 1 and t = 2 have a one-to-one correspondence with the quadratic Gauss sums that decompose the T gate magic state's discrete Wigner function, which are operationally and cost-wise equivalent to the stabilizer rank.…”
supporting
confidence: 53%
See 4 more Smart Citations
“…In this direction, we previously showed that odd-primed dimensional qudit T gate magic states have the same stabilizer rank for t = 1 and t = 2 as has been found for qubits up to the exponential base factor-2 αt ↔ d αt , i.e. (χ 1 ) t = d t and (χ 2 ) t = d 0.5t [9]. In fact, we proved that stabilizer decompositions that achieve these stabilizer ranks for t = 1 and t = 2 have a one-to-one correspondence with the quadratic Gauss sums that decompose the T gate magic state's discrete Wigner function, which are operationally and cost-wise equivalent to the stabilizer rank.…”
supporting
confidence: 53%
“…see Eq. 5) [9]. Hence, ξ 1 = ξ 2 = 3, which leads to tensor bounds of ξ t ≤ (ξ 1 ) t = 3 t and ξ t ≤ (ξ 2 ) t/2 = t 0.5t , for even t.…”
mentioning
confidence: 96%
See 3 more Smart Citations